Design and development of a membrane-based energy recovery systm integrated with turbine ventilator for building application in hot-humid climate. - Ahmad, Mardiana Idayu (Universiti Sains Malaysia, 2017)
This project involves development of a novel energy recovery device coupled with turbine ventilator,and and its intergration to become one system with multifunction (hybrid design) in order to achieve integrated energy-efficient technology for building air-conditioning in hot-humid climate which is called hybrid erv. It consists of two phases in delivering the methodology framework which are: 1) design and development of a membrane-based energy recovery unit for building air-conditioning in hot-humid climate; and 2) performance investigation of integrated membrane-based energy recovery with turbine ventilator for building air-conditioning in hot-humid climate. The integrated design uses advanced materials and could provide the roof ventilation to negate heat and moisture problems for air-conditioned buildings and allow part of the energy from the return airflow to be recovered, thus improving energy efficiency and reducing environmental impact this research contributes to the knowledge of energy recovery for building applications as well as a greater insight into the coupling of the energy recovery in a mix-integrated energy-efficient system to achieve good indoor air quality and energy conservation.